Cross-Ccultural adaptation and psychometric properties of the spanish version of the OPQOL-brief - Perogil Barragán, Natalia.; Gómez Paniagua, Santiago.; Rojo Ramos, Jorge.; González Becerra, María José.; Barrios Fernández, Sabina.; Gianikellis, Konstantinos; Castillo Paredes, Antonio Jonathan.; Carvajal Gil, Julián.; Muñoz Bermejo, Laura. (MDPI, 2023)
Background: Ageing and its consequences on quality of life is one of the main issues to be addressed by public organizations; therefore the development of tools for its evaluation is a priority issue to orientate lines of action. Therefore, the objective of this research is to carry out cross-cultural adaptation and present the psychometric properties of the Spanish version of the Older People’s Quality of Life Questionnaire-Brief (OPQOL-Brief). Methods: a cross-cultural adaptation was carried out together with a process of translation and back-translation of the scale. The OPQOL-Brief and a sociodemographic questionnaire were administered to 120 older adults aged over 65 from a healthcare setting in the region of Extremadura. Results: the exploratory analysis revealed a factor structure through a matrix of polychoric correlations divided in two intercorrelated factors, consisting of 12 items and with excellent sample adequacy indices (KMO = 0.846’; Bartlett test = 1268.1; p = 0.000). Then, the confirmatory factor analysis established the definitive model with exceptional goodness-of-fit indices (NNFI = 0.99; CFI = 0.99; CMIN/DF = 0.96; Ρ (χ2) = 0.22; RMSEA = 0.037 and RMSR = 0.040). Finally, Cronbach’s alpha and McDonald’s omega for internal consistency reported good values of 0.830 and 0.851, respectively. Conclusion: our findings show that the OPQOL-Brief exhibits a solution with 12 elements and related constructs, providing stable goodness-of-fit indicators as well as good and remarkable consistency ratings.
Keywords: Older adults; OPQOL-Brief; Transcultural adaptation; Calidad de vida; Validación